Aleutian Islands Housing Authority Trip Report: St. Paul Island, False Pass and King Cove Assessment of Mold and Moisture Conditions - Francisco, Paul; Nemeth, Robert (Building Research Council. School of Architecture. College of Fine and Applied Arts. University of Illinois at Urbana-Champaign, 2004)
Paul Francisco, Building Research Council (BRC) at the University of Illinois UrbanaChampaign and Robert Nemeth, Magna Systems, Inc. conducted a combined site visit to the St. Paul, False Pass, and King Cove Communities on August 16-20, 2004. The Aleutian Island Housing Authority (AIHA) administers the housing program for the Aleutian and Pribilof Communities. The site visit provided technical assistance to AIHA in assessing mold and moisture conditions in housing units. This report summarizes the activities and issues addressed. A detailed analysis of findings and recommendations is found in PART II: Aleutian Island Housing Authority (St. Paul Island, False Pass, and King Cove) Technical Housing Assessment Report: Examining Mold and Moisture Conditions of Homes for the Aleutian and Pribilof Communities. Made available in DSpace on 2014-09-23T21:46:45Z (GMT). No. of bitstreams: 2 license.txt: 4922 bytes, checksum: 910b249b4beec47e7ab768910c8f966f (MD5) 1206812_2004_building_research_council_aleutian_islands_opt.pdf: 26241779 bytes, checksum: ce39f2b15a190827aded7d265ad238aa (MD5) Previous issue date: 2004 U.S. Department of Housing and Urban Development, Office of Native American Programs